Potential of Mangrove Species for Protecting Mentawai and Sumatra Coasts from Megathrust Hazards: A Systematic Review - Ahmad Taufiq; Alponsin (Universitas Andalas, 2026)
Coastal communities of Mentawai and western Sumatra face recurrent tsunami and erosion hazards associated with the Sunda megathrust. This systematic review evaluated mangrove taxa with evidence relevant to coastal protection. A semantic search in Elicit, covering Semantic Scholar and OpenAlex, identified 1,000 records. Screening followed PRISMA 2020: 993 records were excluded at the title and abstract stage, seven reports were sought, four full texts were assessed, and two studies met the eligibility criteria. Data were synthesized narratively because of heterogeneity in location, threat, and outcome metrics. A post-tsunami field survey from Sri Lanka reported that mature Rhizophora, Sonneratia, and Bruguiera stands resisted extreme hydrodynamic forces, with no adult true mangrove trees uprooted. An Indonesian study from Bengkalis Island found the greatest wave reduction factor for Nypa fruticans (0.0081 to 0.0087 m-1 at a 6 second period), followed by red mangrove, whereas Avicennia marina performed least effectively and had high offshore mortality. The evidence indicates complementary functions rather than a single universally superior species. Rhizophora species appear suitable for structurally exposed fringes, while Nypa fruticans may strengthen estuarine and landward zones through wave attenuation, sediment trapping, and rapid recovery. However, only two heterogeneous studies were included, neither conducted in Mentawai. Local hydrodynamic modeling and field trials are required before implementation.